Alcohol, Cigarette, and Cannabis Use Between 2002 and 2016 in Pregnant Women From a Nationally Representative Sample. Issue 3 (September 2019) - Agrawal, A.; Rogers, C.E.; Lessov-Schlaggar, C.N.; Carter, E.B.; Lenze, S.N.; Grucza, R.A.
Abstract : ( JAMA Pediatr . 2019;173(1):95–96) In the National Survey of Drug Use and Health, the prevalence of cannabis use in pregnant women aged 18 to 44 years rose from 2.37% in 2002 to 3.85% in 2014. Corresponding rates of alcohol use (eg, 11.2% from 2001 to 2005 vs. 10.2% from 2011 to 2013) and cigarette smoking (eg, 13.3% in 2002 vs 12.3% in 2010) during pregnancy have declined. The purpose of this study was to provide more detailed characterization of patterns of substance use during pregnancy.